Minimally Invasive but Maximally Obstructive: Carcinoma In Situ Obstructing a Mainstem Bronchus. Issue 1 (January 2017) - Coiffard, Benjamin; Laroumagne, Sophie; Plojoux, Jérôme; Garcia, Stéphane; D'Journo, Xavier B.; Astoul, Philippe; Dutau, Hervé
Abstract : Here we report a case of mainstem bronchus obstruction due to a carcinoma in situ. Preinvasive lesions, such as carcinoma in situ, are usually small and limited to the bronchial wall. This exceptional presentation shows a tumor growth large enough to completely occlude the right mainstem bronchus. The endoluminal lesion was removed using rigid bronchoscopy. The patient, not eligible for a local treatment, has been treated with surgery.